Respuesta :

Answer:

x = 3

Step-by-step explanation:

Simplifying

4 + -7x = 1 + -6x

Solving

4 + -7x = 1 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.

4 + -7x + 6x = 1 + -6x + 6x

Combine like terms: -7x + 6x = -1x

4 + -1x = 1 + -6x + 6x

Combine like terms: -6x + 6x = 0

4 + -1x = 1 + 0

4 + -1x = 1

Add '-4' to each side of the equation.

4 + -4 + -1x = 1 + -4

Combine like terms: 4 + -4 = 0

0 + -1x = 1 + -4

-1x = 1 + -4

Combine like terms: 1 + -4 = -3

-1x = -3

Divide each side by '-1'.

x = 3

Simplifying

x = 3